TEACHERS' INNOVATIVE READINESS AND SOCIO-PSYCHOLOGICAL CLIMATE OF PEDAGOGICAL COLLECTIVES OF HIGHER EDUCATIONAL INSTITUTIONS - Inna B Avakyan; Galina A Vinogradova (Peoples' Friendship University of Russia (RUDN University), 2018)
In connection with the changes taking place in the modern education system, there is a growing need for the development and use of innovative technologies by university professors, who, however, are not always ready for such innovations. The main objective of the study presented in the article is to identify the relationship between the level of the innovative readiness of university teachers and the peculiarities of the socio-psychological climate of pedagogical collectives of higher educational institutions (which is considered as one of the possible factors of innovative readiness). The study involved the pedagogical collectives of nine higher educational institutions of Russia. The total number was 2036 teachers with experience of pedagogical work from 5 to 40 years (1252 women, 784 men). The psychodiagnostic toolkit included various methods: the express methodology "Evaluation of the socio-psychological climate in the team" (A.Yu. Shalyto, O.S. Mikhalyuk), the Inventory of innovative staff readiness (V.V. Panteleeva, T.P. Knysheva), the diagnostics technique of the personality motivation for success by T. Ehlers. The mathematical and statistical methods of processing the obtained data included the one-sample Kolmogorov-Smirnov test, the Spearman rank correlation coefficient, the linear regression method. The conducted research made it possible to identify the presence of a favorable socio-psychological climate, an average level of the innovative readiness and a sufficiently high level of motivation for success in the majority of the pedagogical collectives of higher education institutions that are represented. A positive correlation between the innovative readiness and the socio-psychological climate of pedagogical collectives of the higher educational institutions has been established, which is confirmed by the results of the linear regression analysis (the higher the level of the socio-psychological climate, the higher the level of innovative readiness). The results obtained can be used as a basis for purposeful work on the psychological and pedagogical support of the innovative activity of teachers in the conditions of maintaining a favorable social and psychological climate in the pedagogical collective.